Correction: Poly(acrylic acid)-mediated synthesis of cerium oxide nanoparticles with variable oxidation states and their effect on regulating the intracellular ROS level. Issue 40 (8th October 2021) - Ju, Xiaohui; Kalbacova, Marie Hubalek; Šmíd, Břetislav; Johánek, Viktor; Janata, Martin; Dinhová, Thu Ngan; Bělinová, Tereza; Mazur, Michal; Vorokhta, Maryna; Strnad, Ladislav
Abstract : Correction for 'Poly(acrylic acid)-mediated synthesis of cerium oxide nanoparticles with variable oxidation states and their effect on regulating the intracellular ROS level' by Xiaohui Ju et al., J. Mater. Chem. B, 2021, 9, 7386–7400, DOI: ; 10.1039/D1TB00706H .